4 - Parcours de la première génération de leaders politiques en Casamance : affirmation identitaire et luttes politiques au Fuladu1 (1946-1958) - Mouhamadou Moustapha Sow, (Afrika Zamani, 2022)
This article retraces the life and political struggles of three pioneering figures of the political scene in the Fuladu (Casamance). They are Amadou Lèye Diop nicknamed “Diop Michel”, Yoro Kandé and Demba Koita; all members of the Senegalese Progressist Union (UPS). From 1948 to 1958, they played key roles in the political life of Fuladu. Among the most central factors that explain their itinerary, one can retain colonial schooling and family heritage. This study aims to comprehend how these two factors have, in different ways, framed the political and professional career of each of these three leaders, and how these in turn have determined their positioning strategies in various deliberative and representative spheres at the local and national levels.